2019
DOI: 10.1039/c9cp01848d
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the solvation and dynamic behaviors of a lithium salt in organic- and ionic liquid-based electrolytes

Abstract: Fundamental molecular insights were provided to understand the advantages of IL solvent electrolytes with high conductivity over organic solvent electrolytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…where B ij = 1 if ions i and j are inside the first coordination shell of each other; otherwise, B ij = 0. As mentioned in our previous studies, there was an anion driving effect in the IL electrolytes, i.e., lithium ions mainly interacted with anions of IL in the electrolyte solution (Tong et al, 2019). Therefore, in this section, as shown in Figure 4, we studied the effect of four lithium salt concentration on the structure and interaction of Li ions with anions in ILs by radial distribution function, coordination number, residence time, ion association trend, and solvation effect.…”
Section: Structural Analysesmentioning
confidence: 90%
See 2 more Smart Citations
“…where B ij = 1 if ions i and j are inside the first coordination shell of each other; otherwise, B ij = 0. As mentioned in our previous studies, there was an anion driving effect in the IL electrolytes, i.e., lithium ions mainly interacted with anions of IL in the electrolyte solution (Tong et al, 2019). Therefore, in this section, as shown in Figure 4, we studied the effect of four lithium salt concentration on the structure and interaction of Li ions with anions in ILs by radial distribution function, coordination number, residence time, ion association trend, and solvation effect.…”
Section: Structural Analysesmentioning
confidence: 90%
“…In Figure 2, the trends of density with concentration of LiTFSI were linear; meanwhile, viscosity was almost exponential for all IL electrolytes in this work. We previously reported that due to their strong interactions between Li + and TFSI − , adding lithium salt LiTFSI to the electrolyte led to the increase of density (Tong et al, 2019). Meanwhile, for a common cation ([C 2 mim] + or [C 4 mim] + ), [TFSI] − -type IL electrolytes had higher density and viscosity than [FSI] − -type IL electrolytes.…”
Section: Physicochemical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Room temperature ionic liquids (ILs) exhibit prominent properties such as negligible volatility, incombustibility, and high chemical and thermal stability compared to conventional organic solvents, [13] which make them attractive for technological applications as electrolytes in energy conversion and storage devices [14–16] . Since Yang et al [17] .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that a variety of RTILs are widely used in EDLCs, our understanding of the behavior of RTILs at charged interfaces remains elusive [27]. Most surging focus is on the role of steric and electrostatic forces in the behavior of ionic liquids [28,29], which are much stronger than that in usual electrolytes. However, the effects of the intermolecular dispersion force on the EDL structures and capacitances have been less explored.…”
Section: Introductionmentioning
confidence: 99%